Comparative evaluation of micronutrient status in the serum of diabetes mellitus patients and healthy individuals with periodontitis - Thomas, Biju (Medknow Publications, 2010)
BACKGROUND: Periodontal diseases are microbial induced chronic inflammatory conditions characterized by infiltration of leukocytes, loss of connective tissue, alveolar bone resorption, and formation of periodontal pockets. In response to periodontal pathogens, the leukocytes (PMN) elaborate destructive oxidants, proteinases and other factors. The balance between these factors, the antioxidants and endogenously synthesized antiproteinases determine the extent of periodontal damage. Diabetes mellitus is a metabolic disorder. Most of the complications of diabetes are due to hyperglycemia. Persons with diabetes are at a greater risk for periodontal disease Malnutrition is characterized by marked tissue depletion of antioxidant nutrients and impaired acute phase protein response to infections resulting in impaired healing. Diabetes mellitus also alters the micronutrient levels. Malnutrition is characterized by marked tissue depletion of antioxidant nutrients and impaired acute phase protein response to infections resulting in impaired healing. Malnutrition, which usually involves concomitant deficiencies of several essential macro and micro nutrients, therefore, has the potential to adversely influence the prognosis of periodontal infections. Objectives:This study has been conducted to evaluate and compare the serum levels of vitamin C, zinc and copper in diabetic and healthy individuals with periodontitis. MATERIALS AND METHODS: In this case control study 60 subjects inclusive of both sexes were selected and divided into 3 groups of 20 each. Group 1 comprised of 20 subjects with type 2 diabetes mellitus and periodontal disease, Group 2 comprised of 20 healthy subjects with periodontal disease. And Group 3 comprised of 20 healthy subjects without periodontal disease. Venous blood samples were collected and centrifuged at 3000rpm for 15 minutes and the superanatant serum is collected to measure the vitamin C, zinc and copper levels. The vitamin C levels of clinical samples were measured using spectrophotometric quantitation (dinitrophenyl hydrazine method) and zinc and copper levels were measured using atomic absorption spectrophotometry. RESULTS: The results showed that the levels of vitamin C and zinc decreased and copper levels increased in diabetic patients with periodontits compared to healthy individuals with periodontitis. CONCLUSION: It may be reasonable to suggest vitamin and/or mineral supplements for patients whose nutrition might be inadequate. Future research should focus on an evaluation of which nutrients may help to prevent the onset and progression of periodontal disease